Analysis of the Application of Problem-Based Learning to Improve Creative Thinking Abilities in Economic Business Student - Bahtiar Efendi; Samuel PD Anantadjaya; Irma M Nawangwulan; Eni Candra Nurhayati; Abdurohim Abdurohim (Edumaspul: Jurnal Pendidikan, 2023)
The purpose of this research is to analyze the application of problem-based learning to improve creative thinking abilities in economics and business student. This research is classroom action research carried out at Medan City Private Universities in the odd semester 2023-2024. The informants in the research are 10 economics and business students at Medan City Private Universities in the odd semester 2023-2024. Data analysis in this research uses qualitative descriptive. The steps for implementing this research consist of planning, implementation, observation, and reflection. The research results show that problem-based learning can improve creative thinking abilities in economics and business student at Medan City Private Universities in the odd semester 2023-2024.